Peter Drucker's five most important questions enduring wisdom for today's leaders - Drucker, Peter F. 1909-2005; Hesselbein, Frances (Wiley, 2015)
Enduring Management Wisdom for Today's Leaders From Peter F. Drucker. provides insightful guidance and stirring inspiration for today's leaders and entrepreneurs. By applying Drucker's leadership framework in the present context of today's leaders and those who lead with them, this book is an essential resource for people leading, managing and working in all three sectors?public, private and social. Readers will gain new perspectives and develop a solid foundation upon which to build a successful and bright future. They will learn how to focus on why they are doing what they're doing, how to do it better, and how to develop a realistic, motivational plan for achieving their goals. This brief, clear, and accessible guide? peppered with commentary from distinguished management gurus, contemporary entrepreneurs and dynamic millennial leaders?will challenge readers and stimulate spirited discussion and action within any organization, inspiring positive change and new levels of excellence. In addition to contributions from Jim Collins, Marshall Goldsmith, and Judith Rodin, the book features new insights from some of today's most influential leaders in business (GE and Salesforce.com), academia (Harvard Business School and Northwestern University), social enterprise (Levo League, Pencils of Promise and Why Millennials Matter) and the military (United States Military Academy), who have been directly influenced by Drucker's theory of management.
Includes bibliographical references. - Print version record
Keywords: Leadership